2011
DOI: 10.1093/arclin/acr018
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Data for the Revised Token Test in Normally Developing Mexican Children Ages 4–12 Years

Abstract: Language comprehension is vital to social and educational development but few pediatric tests are available for its assessment. To approach this problem, two versions of the Token Test (TT), "TT short form" (DeRenzi & Faglioni, 1978) and "Revised Token Test" (RTT), were first compared. Using a sample of 88 normally developing Spanish-speaking children, the tests were compared on their: (a) established psychometric development and (b) internal consistency. The RTT was judged to be superior and was selected for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…This finding indicates that the test items had a good correlation pattern, however not being redundant. We didn't find studies in Brazil which analyzed the test internal consistency, notwithstanding our results are similar to those from Gallardo et al 20 and Spellacy and Spreen 21 . In controls, the test was significantly correlated with education and depressive symptoms, but not with age.…”
Section: Discussionsupporting
confidence: 83%
“…This finding indicates that the test items had a good correlation pattern, however not being redundant. We didn't find studies in Brazil which analyzed the test internal consistency, notwithstanding our results are similar to those from Gallardo et al 20 and Spellacy and Spreen 21 . In controls, the test was significantly correlated with education and depressive symptoms, but not with age.…”
Section: Discussionsupporting
confidence: 83%
“…These results are consistent with normative studies of this version of the Token Test in children (Malloy-Diniz et al, 2007) and adults (Aranciva et al, 2012, Peña-Casanova et al, 2009, as well as in normative studies of the revised version of the Token Test in children (Gallardo et al, 2011). Several studies have demonstrated the absence of gender differences in children's language skills.…”
Section: Discussionsupporting
confidence: 88%
“…The majority of studies have normative data for adults (Aranciva et al, 2012;De Renzi & Faglioni, 1978;Peña-Casanova et al, 2009), to the exception of a study conducted by Malloy et al (2007) who obtained normative data for children between the ages 7 and 10. The limited number of normative studies of the Token Test in children and adolescents focus mostly on the revised version of the Token Test (Gallardo et al, 2011;Kumar, Kumar, & Kumari, 2013). Since the number of subtest and commands varies between versions, it is difficult to compare the results of the present study with those of these studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is a lack of normative data available for all of these tests, especially for Spanish language speakers. Some norms for Spanish speaking children and adolescents can be found here (Armengol, 2002;Esperanza, 2008;Díaz et al, 2012;Galindo, Balderas, Salvador, & Reyes, 2010;Gallardo et al, 2011;Martín et al, 2012;Nieto, Galtier, Barroso, & Espinosa, 2008;Ostrosky-Solís et al, 2007;Rosselli et al, 2004;Servera & Cardo, 2007). However, the majority of Spanish speaking countries do not have country-specific cultural and normative parameters for almost all neuropsychological tests (Wang et al, 2011;Arango-Lasprilla et al, 2016).…”
mentioning
confidence: 99%